A complexity reduction of ETSI advanced front-end for DSR - Li, Jinyu (Proc. ICASSP, 2004)
In Oct. 2002, Advanced Front-End (AFE) for Distributed Speech Recognition (DSR) was standardized by ETSI. In order to use AFE feature on low computational resource devices, we propose a novel approach to improve the computational efficiency. In our new algorithm, the structure of two-stage melwarped Wiener filtering algorithm, which is the main part of AFE, is modified. Wiener filter is constructed and applied directly in mel-warped filter-bank domain. The measures we take make many time-consuming operations in original algorithm completely unnecessary, including the re-calculations of power spectrum and the time-domain convolution operations. Consequently, a large amount of computations are saved. Experiments show that the new approach can substantially reduce the computation load while preserving the excellent performance of the ETSI AFE.